2013
DOI: 10.1177/0969141313510293
|View full text |Cite
|
Sign up to set email alerts
|

Do breast cancer risk factors differ among those who do and do not undertake mammography screening?

Abstract: South Australian women who participated in the population-based mammography screening have a slightly higher prevalence of breast cancer risk factors. This also applies to those who undertook private screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 31 publications
3
24
0
Order By: Relevance
“…[3][4][5][6]12 Such variability is puzzling, and it might be due to the differences in assessment methods or to differences in study samples. 13 If screening allows diagnosis of the disease at an earlier stage, the most appropriate method to evaluate mortality gain would be to assess specific mortality rather than overall mortality. 6 In the present study we found a decrease in BC-specific mortality of 12.4% in screened patients compared with unscreened patients of all age groups, and a reduction of 10% in the unscreened group aged 50-69 years, figures that are similar to our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]12 Such variability is puzzling, and it might be due to the differences in assessment methods or to differences in study samples. 13 If screening allows diagnosis of the disease at an earlier stage, the most appropriate method to evaluate mortality gain would be to assess specific mortality rather than overall mortality. 6 In the present study we found a decrease in BC-specific mortality of 12.4% in screened patients compared with unscreened patients of all age groups, and a reduction of 10% in the unscreened group aged 50-69 years, figures that are similar to our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing the age gradient resulted in slightly higher estimates (14.5% for all BC and 8.3% for IBC) while increasing the slope resulted in lower estimates of overdiagnosis (13.1% and 6.9%, respectively). In further sensitivity analysis in which we adjusted for higher breast cancer risk among screening participants compared with non‐participants based on risk differences noted in a recent survey conducted in SA, estimates of over‐diagnosis were considerably lower than in the original unadjusted analysis. For example, estimates of over‐diagnosis were 1% for IBC and 8% for IBC and DCIS combined after adjustment for 10% higher breast cancer risk among screening participants.…”
Section: Resultsmentioning
confidence: 94%
“…Although we adjusted our estimates for SEP (at the neighbourhood level) and area of residence in our logistic regression models, other potential confounders could not be included due to lack of data at the individual level. Recent surveys examining differences in breast cancer risk profiles among SA women indicated higher prevalence of several breast cancer risk factors among breast screen participants compared with non‐participants . BSSA participants were more likely to have had a family history of breast cancer, higher prevalence of past or current hormone replacement therapy (HRT) use and increased frequency of breast biopsy or breast surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a family history of breast cancer is also known to increase breast density and has been suggested to increase screening participation . Screening participation is also higher in women with a high socio‐economic status, which appears to be associated with dense breasts as well .…”
Section: Discussionmentioning
confidence: 99%